Resettlement & Namibian San communities: prospectives for sustainable community development through empowerment - McLean, Bernice (Department of Environmental and Geographical Science, 2024)
Namibia's Resettlement Programme aims to uplift all Namibians through the redistribution of land. This land reform programme seeks to assist the destitute and landless to become self-sufficient within five years. Policy provisions commit to providing special attention to San people as the most marginalised Namibian community. A critical evaluation of the resettlement process, however, reveals that this is simply rhetoric. Project planning and design is centralised and is undertaken on an ad hoc basis. Resettlement is enabled by rigid, prescriptive and exclusive legislation which has informed the technocratic manner in which the resettlement process is implemented. The authoritative approach adopted to resettlement is goal oriented. It focuses on the short-term product of poverty alleviation, rather than the process of self-sufficiency through empowerment for settlers. This provision of assistance fulfils only the immediate basic needs of settlers as are determined by authorities. The ability of San settlers to achieve autonomy through resettlement is restricted by the incapacity of the process to adapt to diverse social dynamics and locally conceived priorities. Community-level implementation of resettlement remains in the hands of authorities entrenching the continued dependency of San settlers on government provisions. Forced integration of settlers of different social groups whilst disregarding diverse local priorities, fuels social tensions and reduces community cohesion on the projects. The subordination and impoverishment of San settlers is magnified through resettlement. Negative preconceptions compound communication problems on the resettlement projects. Assistance empowering San settlers to improve their well-being, relate to a more community-based approach, identifying and acting on local needs and aspirations. San settlers continue to diversify their livelihood strategies to overcome the challenges posed by their circumstances. The inability of the resettlement process to accommodate these strategies results in a socially, economically and environmentally unsustainable land reform process.